Metal–organic frameworks in pursuit of size: the development of macroscopic single crystals. Issue 20 (12th May 2022) - Rodrigo, Guillermo; Ballesteros-Garrido, Rafael
Abstract : The pursuit of macroscopic MOF crystals: an instructive guide. Abstract : Metal–organic frameworks are versatile structures with many different applications, from industry to the clinic. Despite multiple synthesis approaches being able to coordinate metals and organic ligands, some common strategies can be employed when the size of the final product is a target. Here, we review the most relevant examples of synthesized crystals of very large size ( i.e., macroscopic, in the scale of mm), emphasizing the critical parameters that impact the final crystal size and quality. This compiled knowledge is intended to be an instructive guide to achieve such crystallizations.